Comparative transcriptome and proteome provide new insights into the regulatory mechanisms of the postharvest deterioration of Pleurotus tuoliensis fruitbodies during storage. (September 2021) - Wu, Mu-Xiu; Zou, Yuan; Yu, Ying-Hao; Chen, Bai-Xiong; Zheng, Qian-Wang; Ye, Zhi-Wei; Wei, Tao; Ye, Si-Qiang; Guo, Li-Qiong; Lin, Jun-Fang
Graphical abstract: Highlight: Laccase is the dominant contributor to the browning of P. tuoliensis in PPOs. Only HSP60 and Mn-SOD interactions work in the ROS scavenging system of P. tuoliensis deterioration. Cell cycle arrest and gene expression disorder occurred in P. tuoliensis deterioration. Abstract: The Pleurotus tuoliensis ( Pt ), a precious edible mushroom with high economic value, is widely popular for its rich nutrition and meaty texture. However, rapid postharvest deterioration depreciates the commercial value of Pt and severely restricts its marketing. By RNA-Seq transcriptomic and TMT-MS MS proteomic, we study the regulatory mechanisms of the postharvest storage of Pt fruitbodies at 25 ℃ for 0, 38, and 76 h (these three-time points recorded as groups A, B, and C, respectively). 2, 008 DEGs (Differentially expressed genes) were identified, and all DEGs shared 265 factors with all DEPs (Differentially expressed proteins). Jointly, the DEGs and DEPs of two-omics showed that the category of the metabolic process contained the most DEGs and DEPs in the biological process by GO (Gene Ontology) classification. The top 17 KEGG (Kyoto Encyclopedia of Genes and Genomes) pathways with the highest sum of DEG and DEP numbers in groups B/A (38 h vs. 0 h) and C/A (76 h vs. 0 h) and pathways closely related to energy metabolism were selected for analysis and discussion. Actively expression of CAZymes (Carbohydrate active enzymes), represented by laccase, chitinase, and β-glucanase, directly leads to the softening of fruitbodies. The transcription factor Rlm1 of 1, 3-β-glucan synthase attracted attention with a significant down-regulation of gene levels in the C/A group. Laccase also contributes, together with phenylalanine ammonia-lyase (PAL), to the discoloration reaction in the first 76 h of the fruitbodies. Significant expression of several crucial enzymes for EMP (Glycolysis), Fatty acid degradation, and Valine, leucine and isoleucine degradation at the gene or protein level supply substantial amounts of acetyl-CoA to the TCA cycle. Citrate synthase (CS), isocitrate dehydrogenase (ICDH), and three mitochondrial respiratory complexes intensify respiration and produce high levels of ROS (Reactive oxygen species) by significant up-regulation. In the ROS scavenging system, only Mn-SOD was significantly up-regulated at the gene level and was probably interacted with Hsp60 (Heat shock protein 60), which was significantly up-regulated at the protein level, to play a dominant role in antioxidation. Three types of stresses - cell wall stress, starvation, and oxidative stress - were suffered by Pt fruitbodies postharvest, resulting in cell cycle arrest and gene expression disorder.